Atos de fala transfóbicos no ciberespaço : uma análise pragmática da violência linguística - Silva, Danillo da Conceição Pereira (2017)
In the Brazilian society, aggravated by unequal distribution of economic assets, sociocultural and political rights, the issue of gender violence gains particular importance when it talks about the dynamics of production and subordination of certain identities (HALL, 2007). So, as a result of the dictates of a patriarchal and sexist social model, lifes background that do not comply with the matrix of binary gender and current cisgender are relegated to an abject condition, victimized by transphobia, scourge which according to a report from the NGO Transgender Europe (2016), puts Brazil as the leading country in murders of trans people in the world. With no doubt the language while social practice situated assumes a particular role in this panorama. In addition, in dialog with the Gender Studies (FOUCAULT, 1988; BUTLER, 1997, 2000; LOURO, 2000; BENTO, 2006; BORBA; OSTERNANN, 2007, 2008), the objective of this research is to expand the theoretical-analytical emerging in language studies, in a critical perspective in terms of the linguistic violence (SILVA, 2014) of transphobic motivation, performed in the cyberspace thanks to the strength of illocutionary speech acts that take place under certain ritual forms, through the update and (re-) establishment of specific contexts (DURANTI; GOODWIN, 1992; SILVESTREIN, 1993; HANKS, 2008). In order to forward such a proposal, we assume the pragmatics of language, stemming both from the Philosophy of Language (AUSTIN, 1990 [1962]; WITTGENSTEIN, 1975; DERRIDA, 1991a, 1991b; BUTLER, 1997), and the new Pragmatic Linguistic (MEY,1985; 2001; 2014; RAJAGOPALAN, 2010; ALENCAR, 2010; SILVA, 2012). The corpus used in this study are transphobic speech acts conducted in the cyberspace, present in 17 online comments posted on the website G1 news, between the months of June 2015 and June 2016, in three stories related to the staging of the transsexual actress and model Viviany Belleboni, during the 19th edition of the LGBT Pride parade in São Paulo. Based on a qualitative methodology, interpretative and exploratory, we set the concept of contextualization cues (GUMPERZ, 1998 [1982]), in order to analyze the corpus and to answer the following research questions: i) Under which ritual forms is the violence linguistics motivated by transphobia? ii) Which contexts are (re) introduced to confer the illocutionary strength to this particular type of violent speech act? iii) Which contextual positions the aggressors and victims are asked to take place in these linguistic contexts? The results obtained by analysis of this research suggest, roughly, to the restoration of violent contexts, in which emerges from the strength of illocutionary speech of transphobic acts, capable of subordinate and injure trans people through language, relating to a) the anthropological conditions and social abject which the trans population are relegated; b) to the Christian religion and their narratives, which are aimed to domesticate and to control individuals, producing docile bodies and subjects; c) the medical-scientific knowledge and its effects of truth produced by biologists beliefs of the relation between body and identity; d) to the coloniality devices and standardization in operation of transphobia; and e) the boundaries between subtle physically violence and that performed in the language, producing what is called continuum of violence.